Investigation of production costs in manufacturing environment using innovative tools. (2021) - Nandhakumar, S.; Thirumalai, R.; Viswaaswaran, J.; Senthil, TA.; Vishnuvardhan, VT.
Abstract: Material Requirement Planning plays a vital role in manufacturing environment. The cost calculations for a component receive major attention in the MRP and also require skill labour, Knowledge about materials, involvement of various departments etc. In order to reduce the complexity in calculating the manufacturing cost in earlier phase of production. A user-friendly software is developed using object oriented dynamic programming language Python. By giving input parameters like Geometric Section Shape, Density, and Cost per unit weight of the material and other parameters the and production cost for that component is determined.